High-Intensity Intermittent Exercise Performed on the Sand Induces Higher Internal Load Demands in Soccer Players - Cetolin, Tiago; Teixeira, Anderson Santiago; da Silva, Juliano Fernandes; Haupenthal, Alessandro; Nakamura, Fábio Yuzo; Castagna, Carlo; Guglielmo, Luiz Guilherme Antonacci (Frontiers in Psychology, 2021)
This study aimed to examine the acute and training physiological effect of running-based high intensity intermittent training (HIIT) performed at the same relative speed (i.e., 100% PST-CAR) on sand (SAND) and grass (GRASS) in male junior soccer players. Seven Under-23 Brazilian national league (Serie A) soccer players performed on different days a progressive test to exhaustion (Carminatti’s test, T-CAR) and HIIT in either SAND or GRASS surface condition. The HIIT consisted in three 5-minute bout performed at 100% of T-CAR maximal speed (PST-CAR) with 3 minutes of passive recovery between sets. Measurements of oxygen uptake (VO2), heart rate (HR), blood lactate concentration ([La]) and rating of perceived exertion (RPE) were performed during all conditions. The SAND condition elicited significantly higher %VO2peak (94.58 ± 2.73 vs 87.45 ± 3.31 %, p<0.001, d=2.35), %HRpeak (93.89 ± 2.63 vs 90.31 ± 2.87 %, p<0.001, d=1.30), RPE (8.00 ± 0.91 vs 4.95 ± 1.23 a.u., p<0.001, d=2.82) and [La] (10.76 ± 2.37 vs. 5.48 ± 1.13 mmol/L, p<0.010, d=2.84). This study results showed that HIIT performed on the SAND induce higher internal workload in terms of cardiorespiratory, metabolic and perceptual response compared to GRASS when performed at the same relative exercise intensity (i.e., 100%PST-CAR).